Asymmetric Mineralization of the Arytenoid Cartilages in Patients without Laryngeal Cancer - Zan, E. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: Sclerosis of the arytenoid cartilage may be seen as an incidental finding in patients who do not have laryngeal cancer but may also be an early sign of neoplastic infiltration. Our purpose was to determine the frequency of asymmetric mineralization, in particular sclerosis, of the arytenoid cartilages on CT scans in adults who have no history of laryngeal cancer. MATERIALS AND METHODS: Cervical CT scans of 972 consecutive patients seen in our emergency department were retrospectively evaluated. Three hundred twenty-two patients were excluded who were younger than 18 years of age or whose arytenoids could not be reliably seen due to artifacts. Six hundred fifty patients (424 men, 226 women) were assessed, and their arytenoid cartilages were graded as nonmineralized, calcified, sclerotic, or ossified on each side separately. The mean age of patients was 44.3 ± 17.8 years (range, 18–97 years). RESULTS: The frequencies of asymmetric arytenoid cartilage sclerosis, calcification, and ossification were 4.9% (32/650), 4.4% (29/650), and 3.4% (23/650), respectively, with an overall asymmetric mineralization frequency of 12.9% (84/650). Asymmetric sclerosis was more common in women (16/226, 7.1%) than in men (16/424, 3.8%), but the difference was just at statistical significance (P = .05). The rate of unilateral arytenoid sclerosis was 4.6% in all subjects, 6.6% in women, and 3.5% in men. Unilateral sclerosis is much more frequently associated with the left arytenoid than the right. CONCLUSIONS: Asymmetric mineralization of the arytenoid cartilages was seen in 12.9% of our study population. This should be taken into account when evaluating CT scans of patients with laryngeal cancer for arytenoid cartilage invasion to avoid false-positive reads.